Mr. Perancangan Arsitektur Jaringan Berbasis VLAN dan Security Segmentation untuk Optimasi Layanan Self-Service Kiosk dan Guest WiFi pada Restoran XYZ - Cannavaro Francois Sompotan; Masagus Rakhalish Zhafran Pratama; Muhammad Rizaki Zaidan; Johannes Hamonangan Siregar (Universitas Aisyiyah Surakarta, 2026)
The digital transformation of modern restaurants has increased the demand for network infrastructures capable of supporting self-service kiosk and Guest WiFi services simultaneously without compromising the performance and security of operational networks. This study aims to design a Virtual Local Area Network (VLAN)-based network architecture with security segmentation using Access Control Lists (ACLs) to optimize self-service kiosk services while isolating Guest WiFi traffic at Restaurant XYZ. The study employed an experimental simulation approach consisting of network requirements analysis, network topology and VLAN segmentation design, IP addressing scheme development, Inter-VLAN Routing implementation using the IEEE 802.1Q router-on-a-stick technique, ACL deployment, and network connectivity, inter-VLAN communication, and security testing using Cisco Packet Tracer. The experimental results demonstrated a 100% connectivity success rate with 0% packet loss across all tested devices. Inter-VLAN communication operated successfully through the implemented routing mechanism, achieving an average latency of 10–15 ms, while the ACL policies effectively isolated the Guest WiFi network from operational networks, including the Kitchen, Point of Sale (POS), Management, and CCTV segments, according to the defined security policies. The implementation of VLANs and ACLs provided a more structured network segmentation, improved access isolation among services, and supported stable communication for the self-service kiosk service. The proposed architecture offers a secure, efficient, and scalable network model that can serve as a reference for implementing network infrastructures in modern restaurants and other hospitality environments.